Peran Dukungan Sosial Dalam Memitigasi Stress Pada Dewasa Akhir - Ramadhani, Nayla Safira; Faizah, Lailatul; Masdalifah, Sevinda; Mahardika, I Ketut (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to look at the role of social support for late adulthood in mitigating stress. This research uses a literature view which is carried out by looking at several pieces of literature from other articles. The results obtained in this article are that there is some support to mitigate stress in late adulthood, including emotional support (expressions of empathy, concern and attention). Forward encouragement or agreement with the individual's ideas or feelings and positive comparisons with others), followed by instrumental support.